The science of progress - Grimmer-Solem, E; Grimmer-Solem, Erik (1998)
﻿ This thesis reassess the so-called 'Historical School of Economics' of Gustav Schmoller and his colleagues Lujo Brentano, Adolf Held and Georg Friedrich Knapp, analysing the close relationship between the development of historical economics and the rise of social reform in Germany. It reveals that there is little evidence for a cohesive 'Historical School' and suggests that it was not primarily an outgrowth of romantic and historicist currents of thought as is commonly believed. Schmoller and his colleagues were a pragmatic, empirically-inclined group of statistically-trained economists who drew inspiration from the advances made in the natural sciences. Having directly observed the effects of rapid urbanisation, industrialisation, and the rise of labour movements and socialism in Prussia and abroad, they became dissatisfied with classical economic doctrines and laissez-faire, subjecting these to empirical tests and criticism. Drawing inspiration from British reforms and developments throughout Europe, they devised alternative hypotheses and made innovative policy recommendations. They were also important professionalisers of economics, modifying the curriculum, organising professional bodies, and creating new monographs and journals, the latter substantially aided by the interest and generosity of a leading publisher. Using empirical studies, statistics and history as analytical and critical tools, they sought practical solutions to economic and social problems by disseminating information to both the public and government officials through publications, conferences and petitions. They became leading advocates of trade union rights, factory inspection, worker protection laws, education reforms, worker insurance, agricultural reforms, and the democratisation of industrial relations. Their influence on economic and social policy, while indirect, was considerable, especially through government officials. However, the close association of historical economics with reform and social policy also made them a conspicuous target of criticism within academia and politics. Despite this, by the early 1890s the research methods and social legislation they propounded were gaining wider currency not only in Germany but also in Austria.